2016
DOI: 10.1111/dar.12450
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for intimate partner violence perpetration. A cross‐cultural comparison of English and Brazilian male substance users' explanations

Abstract: Introduction and AimsThis paper describes how substance use features in the accounts of intimate partner violence (IPV) perpetrators in treatment in England and Brazil. The aim of the research was to better understand cross cultural constructions of IPV perpetration amongst men in treatment for substance use.Design and MethodsSemi‐structured interviews were conducted with 40 men in community substance use treatment in Sao Paolo, Brazil and London and the South East of England who had reported IPV perpetration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…Similar to other studies , lifetime IPV victimisation reported by participants was also high. This may be because of participants' partners responding in self‐defence, conflicts around substance use or it may also be influenced by reporting bias.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other studies , lifetime IPV victimisation reported by participants was also high. This may be because of participants' partners responding in self‐defence, conflicts around substance use or it may also be influenced by reporting bias.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of men in treatment for substance use in England and Brazil, Radcliffe et al . found three types of narratives leading to IPV: (i) disputes centred on substance use; (ii) uncharacteristic loss of control as a result of alcohol; and (iii) perceived betrayal as a trigger. In narratives from South Africa, Watt et al .…”
mentioning
confidence: 99%
“…While the quantitative data from studies by Gilchrist et al [17] and Watt et al [21] suggested gender symmetry in the rates of IPV victimisation and perpetration experienced, their qualitative data provide a more nuanced contextual understanding, with instances of victimisation of women by male partners characterised as particularly frequent and intense. In a study of men in treatment for substance use in England and Brazil, Radcliffe et al [23] found three types of narratives leading to IPV: (i) disputes centred on substance use; (ii) uncharacteristic loss of control as a result of alcohol; and (iii) perceived betrayal as a trigger. In narratives from South Africa, Watt et al [21] found that IPV was explained by male aggression while using methamphetamine, norms around sex trading and genderbased attitudes endorsing violence against women.…”
mentioning
confidence: 99%
“…Although the scientific literature evidences the existence of an association between psychoactive substance use and intimate partner violence against women, the debates about the consumption of these substances by women who are violated are still incipient, since a large part of the studies an intimate male partner and one who practices violent acts. [35][36] In addition, the possible underreporting of intimate partner violence against women in different health services, as well as the lack of verification of their main associated factors, makes it feasible to conduct research that explores such problems in the community context, which favors the detection of violent acts and possible risk factors pertinent to the daily life of women.…”
Section: Discussionmentioning
confidence: 99%